Towards inclusion? Adaptation in teaching and learning strategies to students with hearing impairments in inclusive classrooms in universities - Richard Maarifa Kaingo (Eureka: Journal of Educational Research, 2026)
This research was motivated by key issues surrounding the integration of students with hearing challenges, prompting an investigation with targeted goals. Thematic analysis within a qualitative framework was employed. The research engaged 22 individuals, comprising 10 faculty members (ranging from tutorial assistants to senior lecturers), 10 students experiencing hearing difficulties (including those who are deaf or hard of hearing), and 2 specialists in educational support. These participants were drawn from both a public and a private university. Results indicated that many faculty held unfavorable views toward instructing students with hearing challenges. Additionally, there was limited application of modified instructional methods tailored for these students in mixed classroom environments. Furthermore, the study highlighted that institutions lacked sufficient readiness for enrolling such students, particularly regarding the suboptimal deployment of supportive devices for those with hearing difficulties. In conclusion, the results suggest a general lack of knowledge about utilizing supportive tools to aid these learners. Faculty often overlooked or minimally addressed the educational requirements of this smaller group during lessons. Moreover, faculty viewed interactions with these students as an additional challenge.